2012
DOI: 10.1088/0029-5515/52/8/083014
|View full text |Cite
|
Sign up to set email alerts
|

Neutronics experiments for uncertainty assessment of tritium breeding in HCPB and HCLL blanket mock-ups irradiated with 14 MeV neutrons

Abstract: Two neutronics experiments have been carried out at 14 MeV neutron sources on mock-ups of the helium cooled pebble bed (HCBP) and the helium cooled lithium lead (HCLL) variants of ITER test blanket modules (TBMs). These experiments have provided an experimental validation of the calculations of the tritium production rate (TPR) in the two blanket concepts and an assessment of the uncertainties due to the uncertainties on nuclear data. This paper provides a brief summary of the HCPB experiment and then focuses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…For the present study, the neutronics experiments have been extended to include blanket materials and coolant to replicate the blanket structure in a mock-up. Similar experiments have previously been performed by European groups on mock-ups of tritium producing fusion reactor blankets [18][19][20]. Therefore, some fusion-fission blanket mockups should be established and 239 Pu production rates can be obtained in more detail.…”
Section: A Study Of 239 Pu Production Rate In a Water Cooled Natural mentioning
confidence: 72%
“…For the present study, the neutronics experiments have been extended to include blanket materials and coolant to replicate the blanket structure in a mock-up. Similar experiments have previously been performed by European groups on mock-ups of tritium producing fusion reactor blankets [18][19][20]. Therefore, some fusion-fission blanket mockups should be established and 239 Pu production rates can be obtained in more detail.…”
Section: A Study Of 239 Pu Production Rate In a Water Cooled Natural mentioning
confidence: 72%
“…The SUSD3D code was used since early 1990s for very various applications, such as: reactor pressure vessel surveillance dosimetry [3]: uncertainty in predicted dosimeter reaction rates and pressure vessel exposition, determination of realistic safety margins and consequently the reactor lifetime predictions; -fission shielding benchmarks [3]: sensitivity and uncertainty in the measured reaction rates were calculated for the several benchmarks from the SINBAD database, such as the ASPIS Iron, ASPIS Iron88 and VENUS-3 pressure vessel dosimetry benchmark; sensitivity/uncertainty pre-and post-analysis of the fusion shielding benchmarks performed at the Frascatti Neutron Generator (FNG) at ENEA Frascatti (sensitivity/uncertainty of the measured fast/thermal activation rates and the tritium production in FNG-Bulk Shield benchmark, FNG-Streaming, FNG-SiC, FNG-Tungsten [5], FNG HCPB and FNG-HCLL tritium breeding modules [6,7] and FNG Copper [8,9] benchmarks); criticality benchmarks (sensitivity to k eff and b eff ): many benchmarks from IRPhE and ICSBEP (KRITZ-2 [10], SNEAK-7A and À7B [11], VENUS-2, etc. ), MYRRHA reactor [12], etc.…”
Section: Examples Of Applicationsmentioning
confidence: 99%
“…The HCPB and HCLL benchmark experiments, performed previously at the Frascati Neutron Generator (FNG) [19] were re-analyzed with the state-of-theart nuclear data libraries JEFF-3.2, FENDL-3.1b, and ENDF/B-VII.1 with focus on the tritium production. It was found that all three evaluations produce similar results.…”
Section: Benchmark Analyses For Specific Shielding and Tritium Breedimentioning
confidence: 99%